PENERAPAN MODEL PJBL BERBANTUAN ALAT PERAGA SIPERNA (SISTEM PERNAPASAN MANUSIA) UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS V SDN 01 PUNTEN BATU - Fitra Andriana; Arina Restian; Ernaz Siswanto (CV. ADIBA AISHA AMIRA, 2024)
Creativity is one of the important skills that students need to develop. One learning method that can be used to increase creativity is the project-based learning model. The PJBL model can be combined with SIPERNA teaching aids and the use of the human respiratory system so that learning becomes more interesting and meaningful for students. This research aims to determine the effectiveness of introducing SIPERNA material or the PJBL model of the human respiratory system in increasing the creativity of class V students at SDN Punten Batu. This type of research uses an experimental method with a pre-test and post-test group design. The research sample consisted of 28 fifth grade students at SDN Punten Batu who were divided into two groups, namely the experimental group and the control group. The experimental group received treatment with Siperna educational material or the PJBL model of the human respiratory system, while the control group received ordinary learning treatment. Data regarding student creativity was collected before and after treatment through creativity tests. The results showed that there was a significant difference between the creativity scores of experimental group students and the control group after being given treatment. This shows that the application of SIPERNA teaching aids and the PJBL model of the human respiratory system is effective in increasing the creativity of class V students at SDN 01 Punten Batu